Comparative Analysis on Carbon Stock of Rubber Trees (Hevea brasiliensis) based on Different Allometric Equation Models (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Rubber tree (Hevea brasiliensis) plantations represent both an economic resource and a potential carbon sink, yet reliable estimation of their carbon storage capacity remains challenging due to variability among allometric models. This study evaluated aboveground biomass and carbon stock in a rubber plantation at Kampung Pasir Dusun, Jeli, Kelantan, Malaysia, using four established allometric equations (Schroth et al., 2002; Castillo et al., 2016; Saragih et al., 2016; Omar et al., 2013). Diameter at breast heigh (DBH) was measured for 1,588 trees within a 9.2 ha plot, and biomass was converted to carbon stock using a standard conversion factor (0.47). Estimated carbon stocks varied widely, ranging from 21.72 MgC/ha (Saragih et al., 2016) to 41.05 MgC/ha (Schroth et al., 2002). One-way ANOVA indicated significant differences among models (p < 0.05), while Tukey's HSD post-hoc test identified Schroth et al. (2002) and Omar et al. (2013) as consistently producing higher estimates compared to Castillo et al. (2016) and Saragih et al. (2016). These discrepancies reflect differences in model calibration, ecological context, and stand conditions. This findings highlight that model selection substantially influences carbon stock estimation, and emphasise the important of employing site-and-species-appropriate equations to minimise systematic error. Accurate carbon accounting in rubber plantations is therefore essential for understanding their contribution to climate change mitigation and for guiding sustainable forest management practices.
Keywords: Rubber trees, carbon stock allometric equation, climate change mitigation